Metabolic profiling of plasma from cardiac surgical patients concurrently administered with tranexamic acid: DI-SPMEâLCâMS analysis - Barbara Bojko; Marcin WÄsowicz; Janusz Pawliszyn (Elsevier, 2014)
A metabolic profile of plasma samples from patients undergoing heart surgery with the use of cardiopulmonary bypass (CPB) and concurrent administration of tranexamic acid was determined. Direct immersion solid phase microextraction (DI-SPME), a new sampling and sample preparation tool for metabolomics, was used in this study for the first time to investigate clinical samples. The results showed alteration of diverse compounds involved in different biochemical pathways. The most significant contribution in changes induced by surgery and applied pharmacotherapy was noticed in metabolic profile of lysophospholipids, triacylglycerols, mediators of platelet aggregation, and linoleic acid metabolites. Two cases of individual response to treatment were also reported. Keywords: Metabolomics, Heart surgery, Cardiopulmonary bypass, Tranexamic acid, Direct immersion solid phase microextraction, LC/MS